SUPEROVULATORY RESPONSE IN SAHIWAL x JERSEY CROSSBRED COWS WITH DIFFERENT DOSES OF FSHp - REDDY, Y V PRIDHVIDHAR; VEERABRAMHAIAH, K; KRISHNA, K MOULI; REDDY, Y RAVINDRA (The Indian Journal of Animal Reproduction, 2015)
Sahiwal x Jersey crossbred cows were superovulated with 250 and 200 mg FSHp from d10 to 13 of PGF2αsynchronized estrous cycle in divided doses and luteolysis on 72h after initiation of superovulatory treatment. Alldonors responded to superovulatory treatment and the mean ovulation rate, embryo recovery rate and anovulatedfollicles in 250 mg and 200 mg FSHp group were 4.67±0.33 and 3.50±0.34 (p
Keywords: Embryo; FSHp; Ovulation; Sahiwal x Jersey crossbred cows; Superovulation